Understanding Aesthetic Experiences of Architectural Students in Vertical and Horizontal Campuses: A Comprehensive Approach - Seda Bostancı; Suzan Girginkaya Akdağ (Journal of Contemporary Urban Affairs, 2020)
The typological features of university campus areas are shaped according to their locations in the city. Campuses in city centres carry great potential for students’ cultural, intellectual and artistic activities, especially for those from the faculty of architecture and design, with close relations to the city. On the other hand, campuses built on the periphery mainly feature horizontal planning characteristics due to the availability of land. The aim of this paper is to develop an approach for measuring architecture students’ aesthetic experience of vertical and horizontal campuses in relation to the sense of place theory. In this exploratory research, using the ‘photo-projective method’, students will be asked to interpret and draw ‘cognitive maps of the places that they are happy to be (defined place) or to see (landscape) on the campus. Based on students’ impressions and experiences, it will be possible to compare aesthetic experiences on vertical and horizontal campuses. Thus, a comprehensive approach for improving campus design according to users’ aesthetic experiences and sense of place rather than building technology, law, development and finance-driven obligations will be introduced.